MELODRAMATIC PLATFORMS: THE AFFECTIVE THEATRE OF POLARIZED POLITICAL STORYTELLING ON SOCIAL MEDIA - Ní Threasaigh, Míchílín; Boler, Megan (AoIR Selected Papers of Internet Research, 2021)
Once a site of promise for democratizing mass communication, the internet has also become a site of problematic information and polarized affect. Contrary to claims that polarization is not necessarily encouraged by social media platforms; our two-year, mixed-methods study of affect and narratives of race and national belonging in social media discourses of the 2019 Canadian and 2020 U.S. federal elections reveals clearly polarized collective political storytelling constructing conflicting meta-narratives marked by a highly affective moralizing tone and clear binaries of us versus them and good versus evil. Surprisingly, there is very little research that has drawn on either narrative emotions analysis or melodrama to understand the kinds of polarization that take place within social media platforms. This talk shares our finding; achieved through our innovative approach to affective discourse analysis developed through iterative, grounded theoretical qualitative study; that discourse communities formed according to social as well as political identities construct these polarized meta-narratives in the genre of melodrama, readily ensuring the emotional engagement of social media users through “sensationalism and predictable plot lines of good battling evil, plots and characters that do not encourage reflection, and refusal of nuance” (Loseke, 2018, p. 517).